Harmonized methodology to assess chronic dietary exposure to residues from compounds used as pesticide and veterinary drug. (2nd January 2019) - Arcella, Davide; Boobis, Alan; Cressey, Peter; Erdely, Holly; Fattori, Vittorio; Leblanc, Jean-Charles; Lipp, Markus; Reuss, Rainer; Scheid, Stefan; Tritscher, Angelika; Van der Velde-Koerts, Trijntje; Verger, Philippe
Abstract: Risk assessments for pesticide and veterinary drug residues in food are performed respectively by the Joint FAO/WHO Expert Meeting on Pesticide Residues (JMPR) and the Joint FAO/WHO Expert Committee on Food Additives (JECFA). The models used by the two Committees to assess chronic dietary exposure are based on different data and assumptions which may be confusing, particularly for risk managers, when the same compound is used to treat plants and animals. This publication details the results of combined chronic dietary exposure assessments for eight compounds used both as pesticide and veterinary drugs. It compares the results from models in use by JMPR and JECFA with those from national estimates performed by 17 countries. Results show that the JECFA model is better reflecting less than lifetime dietary exposure by considering consumption of children and high consumers. The JMPR model is a suitable model for estimating average chronic (lifetime) exposure to residues present in widely and regularly consumed staple commodities. However, it is suitable neither for estimating children's exposure nor more generally for assessing less than lifetime dietary exposure. In order to select the appropriate exposure model related to the occurrence of adverse effects i.e. effects occurring over less-than-lifetime or effects occurring only over lifetime, this paper proposes criteria to match the toxicological profile of the compound and the appropriate exposure scenarios. These approaches will continue to be harmonized to ensure the most scientifically sound basis for the risk assessment for pesticides and veterinary drug residues and consequently for other chemicals in food.